2008
DOI: 10.1074/jbc.m707933200
|View full text |Cite
|
Sign up to set email alerts
|

Creation and X-ray Structure Analysis of the Tumor Necrosis Factor Receptor-1-selective Mutant of a Tumor Necrosis Factor-α Antagonist

Abstract: Tumor necrosis factor-␣ (TNF) induces inflammatory response predominantly through the TNF receptor-1 (TNFR1).Thus, blocking the binding of TNF to TNFR1 is an important strategy for the treatment of many inflammatory diseases, such as hepatitis and rheumatoid arthritis. In this study, we identified a TNFR1-selective antagonistic mutant TNF from a phage library displaying structural human TNF variants in which each one of the six amino acid residues at the receptor-binding site (amino acids at positions 84 -89) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 50 publications
0
66
0
Order By: Relevance
“…Rational design approaches have been previously used to design receptor-selective TNF-␣ variants (35) and TRAIL variants (22,23,26,36). Directed evolution methods employing phage display were also used to generate receptorselective TRAIL variants (37), a receptor-selective TNF␣ antagonist (38), and a LIGHT/LT␤ variant that does not bind DcR3 (39). In addition, selective receptor activation can also be achieved by the use of receptor-specific agonistic antibodies (40,41) or other binding scaffolds (42).…”
Section: Discussionmentioning
confidence: 99%
“…Rational design approaches have been previously used to design receptor-selective TNF-␣ variants (35) and TRAIL variants (22,23,26,36). Directed evolution methods employing phage display were also used to generate receptorselective TRAIL variants (37), a receptor-selective TNF␣ antagonist (38), and a LIGHT/LT␤ variant that does not bind DcR3 (39). In addition, selective receptor activation can also be achieved by the use of receptor-specific agonistic antibodies (40,41) or other binding scaffolds (42).…”
Section: Discussionmentioning
confidence: 99%
“…This molecular crosstalk makes it complicated to elucidate the roles of each TNF receptor in cell proliferation and apoptosis. In order to activate TNFR2 specifically, a TNFR2-specific agonist (R2-7) was generated from a mutated TNF library using phage-display technology (Shibata et al, 2008;Nomura et al, 2009). By using this technology, R2-7 was identified as a TNFR2-selective TNF mutant protein with six amino acid mutations (positions at 29, 31, 32, 145, 146 and 147) from wild-type TNF (wtTNF).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that molecular modifications of proteins such as PEGylation are effective in suppressing immunogenicity, degradation by proteases, and excretion into the urine (24,29). We previously reported that N terminus-specific monoPEGylation of R1antTNF improved in vivo stability (20,21). However, because R1antTNF adopts a homotrimeric structure composed of three monomers, there are three amino groups arising from each N-terminal residue that may be subject to modification by PEG (Fig.…”
Section: Molecular Modification Efficiency Of Scr1anttnfmentioning
confidence: 99%
“…Therefore, to increase the half-life of the protein, we have applied site-specific PEGylation for R1antTNF, which is a modification technique using polyethylene glycol (PEG) developed in our previous work (23)(24)(25). PEGylation significantly improves the in vivo stability and therapeutic effect of R1antTNF without any associated loss of bioactivity (20,21). However, given that R1antTNF exists as a trimeric structure, there are problems such as a reduction in biological activity caused by intermolecular dissociation.…”
mentioning
confidence: 99%
See 1 more Smart Citation